2022
DOI: 10.3389/fmats.2021.793120
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Induced Micro-Strain Evolution in Super Duplex Stainless Steel—Correlative High-Energy X-Ray Diffraction, Electron Backscattered Diffraction, and Digital Image Correlation

Abstract: The local lattice strain evolution during electrochemical hydrogen charging and mechanical loading in 25Cr-7Ni super duplex stainless steel were measured in-situ using synchrotron high-energy x-ray diffraction. Post-mortem electron backscattered diffraction analysis showed that the austenite phase underwent plastic deformation in the near-surface due to hydrogen-enhanced localized plasticity, where the ferrite phase experienced hardening. In bulk regions, the ferrite was the softer phase, and the austenite rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…We have demonstrated compositional differences in the outermost surface in lateral space and depth, showing variations over the ferrite and austenite grains [4][5][6][7]. It was also revealed that hydrogen infusion in the austenite and ferrite phases results in lattice strain evolution [8][9][10][11][12]. Moreover, we provided diffraction evidence for metastable quasihydrides in the austenite phase that form only during hydrogen uptake.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…We have demonstrated compositional differences in the outermost surface in lateral space and depth, showing variations over the ferrite and austenite grains [4][5][6][7]. It was also revealed that hydrogen infusion in the austenite and ferrite phases results in lattice strain evolution [8][9][10][11][12]. Moreover, we provided diffraction evidence for metastable quasihydrides in the austenite phase that form only during hydrogen uptake.…”
Section: Introductionmentioning
confidence: 64%
“…Charge carrier concentration Semiconductor type Tensile strains developed in the outermost surface before hydrogen evolution, and compressive strains developed when hydrogen was infused (more negative than − 0.9 V) into the microstructure. The strain formation was shown in earlier work to adopt a logarithmic dependence with time [8,12]. The lattice strains increase with time, requiring some time to reach near-equilibrium state.…”
Section: E Fbmentioning
confidence: 80%